Neurorestoration of Sustained Attention in a Model of HIV-1 Associated Neurocognitive Disorders - Moran, Landhing M.; McLaurin, Kristen A.; Booze, Rosemarie M.; Mactutus, Charles F. (Frontiers in Behavioral Neuroscience, 2019)
Due to the sustained prevalence of HIV-1 associated neurocognitive disorders (HAND) in the post-cART era, as well as the increased prevalence of older HIV-1 seropositive individuals, there is a critical need to develop adjunctive therapeutics targeted at preserving and/or restoring neurocognitive function. To address this knowledge gap, the present study examined the utility of S-Equol (SE), a phytoestrogen produced by gut microbiota, as an innovative therapeutic strategy. A signal detection operant task with varying signal durations (1000, 500, 100 msec) was utilized to assess sustained attention in HIV-1 transgenic (Tg) and control animals. During the signal detection pretest assessment, HIV-1 Tg animals displayed profound deficits in stimulus-response learning and sustained attention relative to control animals. Subsequently, between 6 and 8 months of age, HIV-1 Tg and control animals were treated with a daily oral dose of either placebo or SE (0.05, 0.1, 0.2 mg) and a posttest assessment was conducted in the signal detection operant task with varying signal durations. In HIV-1 Tg animals, a linear decrease in the number of misses at 100 msec was observed as SE dose increased, suggesting a dose response with the most effective dose at 0.2 mg SE, approximating controls. Comparison of the number of misses across signal durations at the pretest and posttest revealed a preservation of neurocognitive function in HIV-1 Tg animals treated with 0.2 mg SE; an effect that was in sharp contrast to the neurocognitive decline observed in HIV-1 Tg animals treated with placebo. Results support the utility of 0.2 mg SE as a potential efficacious neuroprotective and/or neurorestorative therapeutic for sustained attention, in the absence of any adverse peripheral effects, in the HIV-1 Tg rat. Thus, the present study highlights the critical need for further in vivo studies to elucidate the full potential and generalizability of phytoestrogen treatment for HAND.